Predictive Genetic Testing of Children for Adult‐Onset Conditions: Negotiating Requests with Parents. Issue 2 (28th September 2016) - Fenwick, Angela; Plantinga, Mirjam; Dheensa, Sandi; Lucassen, Anneke
Abstract: Healthcare professionals (HCPs) regularly face requests from parents for predictive genetic testing of children for adult‐onset conditions. Little is known about how HCPs handle these test requests, given that guidelines recommend such testing is deferred to adulthood unless there is medical benefit to testing before that time. Our study explored the process of decision‐making between HCPs and parents. Semi‐structured interviews were conducted with 34 HCPs in 8 regional genetic services across the UK, and data were thematically analysed. We found that instead of saying 'yes' or 'no' to such requests, many HCPs framed the consultation as an opportunity to negotiate the optimal time of testing. This, they argued, facilitates parents' considered decision‐making, since parents' eventual decisions after requesting a test was often to defer testing their child. In cases where parents' requests remained a sustained wish, most HCPs said they would agree to test, concluding that not testing would not serve the child's wider best interest. As a strategy for determining the child's best interest and for facilitating shared decision‐making, we recommend that HCPs re‐frame requests for testing from parents as a discussion about the optimal time of testing for adult‐onset disease.